THE IMPACT OF ENVIRONMENTAL LIABILITIES ON THE STOCK PRICE AND MARKET VALUE - Bae, Benjamin; Michieka, Nyakundi M.; Elhusseiny, Mahdy F. (International Journal of Accounting & Finance Review, 2022)
This study examines the effect on the security returns of a company named on the National Priority List (NPL) for the Superfund site. It investigates if the designation as a potentially responsible party (PRP) generates more negative abnormal returns after listing the NPL. Since this designation of firms as PRPs increase regulatory costs such as cleanup costs and disclosure requirements, an adverse market reaction is expected. This study employs several financial databases, such as Research Insight, CRSP, I/B/E/S, and the EPA's NPL database, which compile the Superfund listing for each firm in the sample. In the case of environmental liabilities, the potential future cost of environmental remediation makes estimating the firm's earnings more difficult. This implies that the earnings of PRP firms may not persist, resulting in noisier accounting information. The empirical results support the hypotheses that the markets react negatively to the bad news that the firm has been designated as a PRP in the Superfund site, implying that environmental liabilities negatively impact firm stock price and valuation. Significant findings provide financial statement users with helpful information about contingent environmental liabilities and help them make more informed investment decisions and better judge the firms' future performance.JEL Classification Codes: G1, G2, G3, M41, M48.